Medicinal Values of Tomato (Lycopersicon esculentum Mill. –Solanaceae) - Mallick, Pushpa Karna (International Journal of Applied Sciences and Biotechnology, 2021)
Lycopersicon esculentum is a flowering plant of the family Solanaceae. The common name for this plant is tomato. Tomatoes are a good source of lycopene which is a main pigment found in it and responsible for red colour. The lycopene provides antioxidant properties and helps to prevent cell damage. Tomatoes also prevent the adverse effects of lead in the blood constituents. Tomatoes are used in different ways such as raw or cooked, in many dishes, sauces, salads, pickles, puree, paste, juice, sun- dried and drink. Tomato fruits content ninety four percent water, citric acid, malic acid, soluble sugars, vitamin, vitamin B1, B2, vitamin A, and many mineral salts etc. High levels of lycopene which contain in tomatoes are used in facial cleanser. Flavonoids like flavonols which is present in tomatoes are rich in antioxidant activity and can help our body ward off every day toxins. Flavonoides such as flavonols present in tomatoes are rich in antioxidant activity and can help our body ward off every day toxins Flavonoides directly associated with human dietary ingredients, play a great role in diseases prevention and shows versatile health benefits. Int. J. Appl. Sci. Biotechnol. Vol 9(3): 166-168.